Real‐world effectiveness of direct‐acting antiviral agents for chronic hepatitis C patients with genotype‐2 infection after completed treatment. Issue 4 (5th November 2020) - Cheng, Tzu‐Sheng; Liang, Po‐Cheng; Huang, Chung‐Feng; Yeh, Ming‐Lun; Huang, Ching‐I; Lin, Zu‐Yau; Chen, Shinn‐Cherng; Huang, Jee‐Fu; Dai, Chia‐Yen; Hsieh, Ping‐Hsin; Chuang, Wan‐Long; Yu, Ming‐Lung
Abstract: Chronic hepatitis C (CHC) is a major cause of cirrhosis, hepatocellular carcinoma (HCC), and mortality. Eliminating hepatitis C virus (HCV) can greatly improve long‐term outcomes. Several direct‐acting antiviral agents (DAAs), including sofosbuvir (SOF) plus different NS5A inhibitors, as well as non‐SOF‐based DAAs, including glecaprevir/pibrentasvir (GLE/PIB), have been approved for treating CHC genotype‐2 (GT‐2) patients in Taiwan. However, there is limited real‐world effectiveness data regarding these different regimens. Thus, we aimed to evaluate the real‐world efficacy in CHC GT‐2 patients who underwent these DAA regimens. We retrospectively enrolled CHC GT‐2 patients who were treated with SOF‐based DAAs or GLE/PIB at a single medical center. A total of 704 enrolled patients were treated with either SOF + ribavirin (RBV), SOF/daclatasvir (DCV) ± RBV, SOF/ledipasvir (LDV) ± RBV, SOF/velpatasvir (VEL) ± RBV, or with GLE/PIB. The overall sustained virological response (SVR) rate was 97.9%. The SVR rate was significantly lower in the SOF + RBV group (95.6%) than in the non‐SOF + RBV (98.9%) group, especially compared to the SOF/DCV (100%) and GLE/PIB groups (99.5%). Among patients treated with SOF + RBV, cirrhotic patients had significantly lower SVR rates than noncirrhotic patients (89.4% vs 98.2%). Multivariate analysis showed that patients with a younger age, hepatitis B virus coinfection, baseline cirrhosis, or those who received SOF + RBV were less likely to achieve SVR. In conclusion, for CHC GT‐2 patients, SOF in combination with DCV, LDV, or VEL, as well as GLE/PIB, achieved similar high efficacies, regardless of cirrhosis, treatment experience, or chronic kidney disease status. Therefore, the use of DAA therapy to eradicate HCV should not be delayed in these populations.